Built-in electric field enhanced ionic transport kinetics in the T-Nb2O5@MoO2 heterostructure. Issue 40 (12th October 2021) - Huang, Huihuang; Zhao, Guangyu; Sun, Xin; Yu, Xianbo; Liu, Chao; Shen, Xiaojie; Wang, Ming; Lyu, Pengbo; Zhang, Naiqing
Abstract : The built-in electric field induced by the T-Nb2 O5 @MoO2 heterostructure facilitates charge transfer and ionic transport kinetics during the cycling process. Abstract : Mg 2+ /Li + hybrid ion batteries (MLIBs) are regarded as an emerging candidate for next generation rechargeable batteries. However, realizing superior high-rate performance is still an unremitting challenge for further development of MLIBs. Herein, a rational design of the T-Nb2 O5 @MoO2 nanorod array heterostructure as the cathode of MLIBs is presented. The resulting heterostructure reinforces structural stability and induces the generation of a built-in electric field, which facilitates ionic transport kinetics, as verified by reaction kinetics analysis, ex situ characterization techniques and density functional theory calculations. As expected, the T-Nb2 O5 @MoO2 heterostructure delivers a reversible capacity of 250.3 mA h g −1 at 0.5C, excellent rate performance (68.8 mA h g −1 at 10C) and long cycling life (capacity retention of 76.0% at 5C after 1500 cycles). Thus, this strategy paves the way for designing advanced electrode materials with excellent electrochemical performance.